Patient experience of home and waiting room blood pressure measurement: a qualitative study of patients with recently diagnosed hypertension - Tompson, A; Schwartz, C; Fleming, S; Ward, A; Greenfield, S; Grant, S; Hobbs, F; Heneghan, C; McManus, R (Royal College of General Practitioners, 2018)
Background: Out-of-office blood pressure (BP) measurement is advocated to confirm hypertension diagnosis. However, little is known about how primary care patients view and use such measurement. Aim: To investigate patient experience of out-of-office BP monitoring, particularly home and practice waiting room BP measurement, before, during, and after diagnosis. Design: and setting A cross-sectional, qualitative study with patients from two UK GP surgeries participating in a feasibility study of waiting room BP measurement. Method: Interviewees were identified from recent additions to the practice hypertension register. Interviews were recorded, transcribed, and coded thematically. Results: Of 29 interviewees, 9 (31%) and 22 (76%) had used the waiting room monitor and/or monitored at home respectively. Out-of-office monitoring was used by patients as evidence of control or the lack of need for medication, with the printed results slips from the waiting room monitor perceived to improve ‘trustworthiness’. The waiting room monitor enabled those experiencing uncertainty about their equipment or technique to double-check readings. Monitoring at home allowed a more intensive and/or flexible schedule to investigate BP fluctuations and the impact of medication and lifestyle changes. A minority used self-monitoring to inform drug holidays. Reduced intensity of monitoring was reported with both modalities following diagnosis as initial anxiety or patient and GP interest decreased. Conclusion: Home and practice waiting room measurements have overlapping but differing roles for patients. Waiting room BP monitors may be a useful out-of-office measurement modality for patients unwilling and/or unable to measure and record their BP at home.